Combined microwave‐assisted extraction and headspace gas chromatography for hexanal determination in fat‐rich food. Issue 5 (17th February 2022) - Vickackaite, Vida; Jurkute, Ingrida; Poskus, Vilius; Bugelyte, Birute
Abstract: The feasibility of a new approach for the determination of volatiles in solid matrices by coupling microwave‐assisted extraction with static headspace gas chromatography has been demonstrated using hexanal as an analyte present in fat‐rich food. Eight polar and low volatility deep eutectic solvents were prepared using microwave heating and examined for hexanal extraction. Choline chloride‐glucose‐water showed the best transition efficiency of hexanal to the headspace and was applied to extract hexanal using microwave‐assisted extraction. Hexanal released from the fat‐rich food is poorly soluble in the hydrophilic deep eutectic solvent choline chloride‐glucose‐water so enters the gas phase and subsequently dissolves in coconut oil fixed above the extraction mixture in a polypropylene capillary. After cooling the capillary was transferred to a headspace vial and headspace gas chromatography was carried out. Under optimized conditions, the limit of detection was 3.1 μg g –1 . The developed approach was successfully applied to analyze hexanal in fat‐rich food.